A relação entre regulação emocional e o consumo de álcool entre jovens universitários - Salmerón, Samantha Faganélli (Universidade Federal de São Carlos, 2024)
In the university context, it is common for social gatherings and student parties to be celebrated with the presence of alcohol for student consumption, where excessive alcohol intake may occur. High alcohol consumption poses a risk to the health and well-being of the person consuming it. Additionally, the behavior of intoxicated individuals can cause physical and emotional harm, ranging from mild to severe, to others. Considering the relationship between high stress levels and abusive alcohol use, it becomes relevant to investigate whether the use of emotional regulation strategies can protect university students from risky behaviors, such as excessive drinking. Therefore, the aim of this study was to examine the relationships between perceived stress, the use of appropriate and dysfunctional emotional regulation strategies, and the pattern of alcohol use among university students. Participants were 69 university students of both genders, between 18 and 51 years of age, and from different levels of higher education. Participants were recruited through social media invitations and they completed instruments regarding sociodemographic questions, perceived stress, the use of different emotional self-regulation strategies, and alcohol consumption. The data was analyzed using the Jamovi software. Positive and statistically significant correlations were found between: (a) perceived stress and the use of appropriate emotional regulation strategies, (b) paralysis or “freezing” (an inappropriate emotional regulation strategy) and alcohol consumption, and (c) externalization of aggression (another inappropriate emotional regulation strategy) and alcohol consumption. In light of these results, it can be inferred that the more stress students experienced, the more they reported using appropriate emotional regulation repertoires. However, the more students reacted to the demands of their lives with paralysis or aggression, the higher their alcohol consumption. The main limitations of this study were the sample size, to verify the association between constructs, as well as a participant sample that mostly reported low alcohol consumption. Thus, this study should be replicated with a sample of at least 200 participants and the use of a different recruitment strategy, so as to include more diverse participants in terms of alcohol consumption. Furthermore, it will be important to assess the use and effects of other ways of coping with stressful situations (e.g., spending time with friends, physical activities, etc.), along with emotional regulation strategies, to determine if healthy behaviors complement emotional regulation strategies in reducing the frequency of alcohol use and other health-damaging behaviors.
The rlationship between emotion regulation and alcohol consumption among university students
Keywords: Autorregulação emocional; Estresse; Abuso de substâncias; Jovens adultos; Estudantes; Consumo de álcool; Emotional self-regulation; Stress; Substance abuse; Young adults; Students; Alcohol consumption; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA